Fort Margherita - Nor Azah Abd Aziz; Rozlan Mohamed Noor (Kuala Lumpur, Malaysia : Utusan Publications & Distributors, 2010)
Prize winning short stories in the 2009 juvenile short stories writing contest of Kumpulan Utusan
1. Kasut Tutankhamun / Fudzail -- 2. Puaka Pak Jaha / Nadia Khan -- 3. Ayam patah kepak / Hanif Hafiza -- 4. Hipertensi / Illias Zaidi -- 5. Khilaf / Wan Marzuki Wan Ramli -- 6. Es teler pagi raya / Ummu Hani Abu Hassan -- 7. Fort Margherita / Mohd. Ali bin Salim -- 8. Munsyi / Mawarni Sulaiman -- 9. Sanubari seorang anak / Siti Hajar Mohd. Zaki
"Pemenang kategori cerpen remaja" -- cover
Short stories
Keywords: Malay fiction; Short stories, Malay; Young adult fiction, Malay